The Gene Expression Analysis of Blood Reveals S100A11 and AQP9 as Potential Biomarkers of Infective Endocarditis - Thuny, Franck; Textoris, Julien; Ben Amara, Amira; El Filali, Adil; Capo, Christian; Habib, Gilbert; Raoult, Didier; Mege, Jean-Louis (PLOS ONE, 2012)
Background The diagnostic and prognostic assessments of infective endocarditis (IE) are challenging. To investigate the host response during IE and to identify potential biomarkers, we determined the circulating gene expression profile using whole genome microarray analysis. Methods and Results A transcriptomic case-control study was performed on blood samples from patients with native valve IE (n = 39), excluded IE after an initial suspicion (n = 10) at patient's admission, and age-matched healthy controls (n = 10). Whole genome microarray analysis showed that patients with IE exhibited a specific transcriptional program with a predominance of gene categories associated with cell activation as well as innate immune and inflammatory responses. Quantitative real-time RT-PCR performed on a selection of highly modulated genes showed that the expression of the gene encoding S100 calcium binding protein A11 (S100A11) was significantly increased in patients with IE in comparison with controls (P<0.001) and patients with excluded IE (P<0.05). Interestingly, the upregulated expression of the S100A11 gene was more pronounced in staphylococcal IE than in streptococcal IE (P<0.01). These results were confirmed by serum concentrations of the S100A11 protein. Finally, we showed that in patients with IE, the upregulation of the aquaporin-9 gene (AQP9) was significantly associated with the occurrence of acute heart failure (P = 0.02). Conclusions Using transcriptional signatures of blood samples, we identified S100A11 as a potential diagnostic marker of IE, and AQP9 as a potential prognostic factor.